The Formosan Primary Anthropogenic Myths, Genesis, and the Creation of Man - Gauss, Valdis, (Asian Studies E-Books Online, Collection 2025, 2025)
In this book, Valdis Gauss anthologizes the Formosan anthropogenic myths from all of Taiwan's Austronesian tribes. Over 250 origin texts, sourced from dozens of linguistic, anthropological, historical, and mythological corpora as well as other publications have been collated and analysed rendering the present literary survey far more comprehensive than any prior study on this subject. Over 100 Formosan myths, many of which were never previously available in English have been translated here for the first time. In the absence of longstanding traditional orthographical records, the Austronesian tribes that inhabit the island of Taiwan have relied on the transmission of oral literatures for the preservation of historical events since the dawn of time. The earliest historical events that are still recited by tribal elders relate to the origins of the gods and first ancestors of mankind. This anthology continues the tradition of collecting and transcribing these myths for everyone interested in the corpus of literature from Taiwan's aboriginal peoples.